1994
DOI: 10.1159/000239310
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Comparison of Ciprofloxacin and Amoxycillin/ Clavulanic Acid in the Treatment of Chronic Sinusitis

Abstract: A total of 251 adults with chronic sinusitis were enrolled into this prospective multicentre, double-blind, double-placebo comparison of ciprofloxacin (500 mg twice daily) with amoxy-cillin/clavulanic acid (500 mg three times daily). The diagnosis of chronic sinusitis (persistence of clinical symptoms for at least 3 months) was confirmed by computerized tomography scan and/or sinusoscopy prior to therapy. Patients at inclusion had purulent or muco-purulent rhinorrhoea. Staphylococcus aureus (n = 45), Haemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 0 publications
3
53
0
2
Order By: Relevance
“…There were a total of four [736][737][738][739] double-blind randomized trials comparing 2 individual antibiotic regimens head to head without the inclusion of a placebo arm. Clinical resolution of RS was the main endpoint in each study, and there was no identifiable difference between treatment arms.…”
Section: Viie4 Crssnp Management: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a total of four [736][737][738][739] double-blind randomized trials comparing 2 individual antibiotic regimens head to head without the inclusion of a placebo arm. Clinical resolution of RS was the main endpoint in each study, and there was no identifiable difference between treatment arms.…”
Section: Viie4 Crssnp Management: Antibioticsmentioning
confidence: 99%
“…Short-term (9 to 14 days) use of antibiotics improved clinical symptoms such as nasal discharge and nasal blockage, and there was no difference in the clinical efficacy of several kinds of antibiotics. [737][738][739] Although there has been no trial directly investigating preoperative antibiotics and intraoperative condition, patient-reported symptoms have been shown to be correlated with intraoperative bleeding and longer surgery time. 1155 Therefore, preoperative oral antibiotics may be beneficial in patients presenting with acute exacerbation of symptom and purulent discharge on endoscopic examination.…”
Section: Xc2 Crssnp: Preoperative Oral Antibioticsmentioning
confidence: 99%
“…In particular, one study showed a clinical response rate of 95% with amoxicillin-clavanulate compared with 88% with cefuroxime when 206 patients with CRS exacerbation were randomized to a 10-day course of either antibiotic therapy; bacteriologic cure rates were 65% and 68%, respectively, in each treatment group. 18 A study by Legent et al 19 showed similar benefit from oral antibiotics when 251 patients with CRSsNP exacerbation were randomized to treatment with either ciprofloxacin or amoxicillin-clavanulate; clinical cure rates were 58% and 51% in each treatment group, respectively, although there was not a statistically significant difference in cure rates between the two groups. 19 In vitro studies also demonstrated the anti-inflammatory and immune-modulatory properties of macrolide antibiotics in influencing neutrophil, eosinophil, and macrophage function.…”
Section: Antimicrobialsmentioning
confidence: 95%
“…18 A study by Legent et al 19 showed similar benefit from oral antibiotics when 251 patients with CRSsNP exacerbation were randomized to treatment with either ciprofloxacin or amoxicillin-clavanulate; clinical cure rates were 58% and 51% in each treatment group, respectively, although there was not a statistically significant difference in cure rates between the two groups. 19 In vitro studies also demonstrated the anti-inflammatory and immune-modulatory properties of macrolide antibiotics in influencing neutrophil, eosinophil, and macrophage function. 20 A study by Wallwork et al, 21 in 2006, evaluated the response of CRS in 64 patients to long-term treatment with roxithromycin 150 mg daily for 12 weeks compared with placebo.…”
Section: Antimicrobialsmentioning
confidence: 95%
“…While not generally considered to be the drugs of first choice, older quinolones have comparable efficacy to cephalosporins and beta-lactams in randomized clinical trials (9). In the treatment of chronic bacterial sinusitis, ciprofloxacin has been reported to be as effective as amoxicillin/clavulanic acid, with clinical resolution and/or improvement reported in more than 80% of patients in both groups (10). The newer fluoroquinolones have been studied in 36E patients with acute bacterial sinusitis because of the drugs' improved activity against all respiratory pathogens.…”
Section: Upper Airway Infectionsmentioning
confidence: 99%